The water and horticulture in Pirapozinho – SP - Aznar, Fábio Eduardo [UNESP]; Rizk, Maria Cristina [UNESP] (Universidade Federal de Goias, 2022)
The article describes the result of a work carried out with small vegetable growers in the municipality of Pirapozinho – SP, whose objective was to diagnose the use of water in the irrigation of vegetables. In the field research, 14 vegetable producers were interviewed, following a semi-structured script. The results of the work indicated the sprinkler irrigation system with micro sprinklers as the most used irrigation system. Groundwater, captured via semi-artesian wells, is the main source of supply, with an estimated average daily withdrawal between 100 liters/day to 5000 liters/day. There is a need to improve irrigation management, since it is carried out based on empirical criteria, not ensuring precision in water distribution, in addition to the need to guide producers on the importance of analyzing the quality of water used in irrigation, since most producers reported never having done it. Improving the use of water in vegetable irrigation in the municipality of Pirapozinho – SP necessarily involves working together with public agencies, rural extension agencies and vegetable producers.
Agua y olericulture en Pirapozinho – SP
A água e a olericultura em Pirapozinho – SP
Keywords: Irrigation; Little growers; Vegetables